Medical experience of a university hospital in Turkey after the 1999 Marmara earthquake. Issue 7 (24th June 2005) - Bulut, M; Fedakar, R; Akkose, S; Akgoz, S; Ozguc, H; Tokyay, R
Abstract : Objectives: This study aimed to provide an overview of morbidity and mortality among patients admitted to the Hospital of the Medicine Faculty of Uludag University, Bursa, Turkey, after the 1999 Marmara earthquake. Methods: Retrospective analysis of the medical records of 645 earthquake victims. Patients' demographic data, diagnosis, dispositions, and prognosis were reviewed. Results: A total of 330 patients with earthquake related injuries and illness admitted to our hospital were included and divided into three main groups: crush syndrome (n = 110), vital organ injuries (n = 57), and non-traumatic but earthquake related illness (n = 55). Seventy seven per cent of patients were hospitalised during the first three days after the earthquake. The rate of mortality associated with the crush syndrome, vital organ injury, and non-traumatic medical problems was 21% (23/110), 17.5% (10/57), and 9% (5/55), respectively. The overall mortality rate was 8% (50/645). Conclusions: In the first 24–48 hours after a major earthquake, hospital emergency departments are flooded with large numbers of patients. Among this patient load, those patients with crush syndrome or vital organ injuries are particularly at risk. Proper triage and prompt treatment of these seriously injured earthquake victims may decrease morbidity and mortality. It is hoped that this review of the challenges met after the Marmara earthquake and the lessons learned will be of use to emergency department physicians as well as hospital emergency planners in preparing for future natural disasters.